2018
DOI: 10.1186/s40510-018-0241-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender and growth variation in palatal bone thickness and density for mini-implant placement

Abstract: BackgroundThe objective was to compare the palatal bone thickness (PBT) and palatal bone density (PBD) in the anterior, middle, and posterior part of the palate in males and females.MethodsThis retrospective study reviewed cone beam computed tomography scans of 359 patients. The scans were divided into 99 growing males, 105 growing females, 74 non-growing males, and 81 non-growing females. The measurements of PBT and PBD were made in between the canine and first premolar, the first premolar and second premolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
7
15
0
Order By: Relevance
“…The hard tissues and hardþsoft tissues of males were thicker than those of females at the P1 and P2 planes. Several studies 7,19 reported that males had significantly greater palatal bone thickness than did females, in accordance with the current results. Manni et al 21 showed that compared to males, the failure risk of mini-implants was significantly higher in females, likey as a result of decreased bone thickness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The hard tissues and hardþsoft tissues of males were thicker than those of females at the P1 and P2 planes. Several studies 7,19 reported that males had significantly greater palatal bone thickness than did females, in accordance with the current results. Manni et al 21 showed that compared to males, the failure risk of mini-implants was significantly higher in females, likey as a result of decreased bone thickness.…”
Section: Discussionsupporting
confidence: 92%
“…6 The median and paramedian areas of the palate consist of thick cortical bone that offers enough bone quality and quantity to support miniimplants. 7 This area has the advantages of having no significant anatomical structures, such as nerves, blood vessels, or roots, that can interfere with the placement of mini-implants. 8 Additionally, palatal regions are suitable for mini-implant insertion as a result of keratinized tissues covering the palatal bones and because there are no or minimal potential soft tissue irritations.…”
Section: Introductionmentioning
confidence: 99%
“…Their study, however, did not differentiate patients according to age or sex. A recent search of literature revealed a study correlating sex and growth variation regarding palatal bone thickness based on only eight measurement points in the palate [34]. Holm et al also differentiated between male and female patients and based their measurements on 40 measurement points projected on the palate [15].…”
Section: Introductionmentioning
confidence: 99%
“…This region was preferred since the greatest bone thickness was reported in the anterior paramedian part of the palatal bone and would therefore be relatively safe for miniscrew insertion. [18][19][20] Since bone thickness in this area varies depending on sex and age, cone-beam computed tomography (CBCT) scans have been recommended before insertion of orthodontic miniscrew. [18][19][20] However, CBCT evaluations were not performed in this study because of its retrospective design.…”
Section: Discussionmentioning
confidence: 99%